State of Human Cord Blood Nucleated Cells After Cryopreservation with DMSO and Antioxidants and Transfer to Conditions Simulating Physiological - Makashova, Olena E.; Zubova, Oksana L.; Zubov, Pavlo M.; Babiychuk, Lubov O. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 039–043